Productivity of agile teams: an empirical evaluation of factors and monitoring processes - Melo, Claudia de Oliveira (2013)
Lower cost and shorter time-to-market expectations are the major drivers of software productivity improvements. To manage productivity effectively, it is important to identify the most relevant difficulties and develop strategies to cope with them. Agile methods, including Extreme Programming and Scrum, have evolved as approaches to simplify software development process, potentially leading to better productivity. They aim to shorten development time and handle the inevitable changes resulting from market dynamics. Although the industry has extensively adopted agile methods, little research has empirically examined the software development agility construct regarding its dimensions, determinants, and effects on software development performance. Understanding this construct could help determine where to concentrate management efforts (and related financial resources) from a practical standpoint and where to focus research efforts from an academic perspective. Considerable research has been directed at identifying factors that have a significant impact on software development productivity. In general, the studied productivity factors were related to product, personnel, project, process, or organizational issues. Continuously evaluating productivity factors is important, as factors may change under new software engineering practices. However, little research has investigated the major factors influencing agile team productivity. ]The goal of this thesis was to explore productivity definitions, factors, and monitoring in agile teams and to improve the practice based on the collected evidence and gained knowledge. This thesis presents five novel contributions: C1 - Empirical verification of the importance of productivity for companies adopting agile methods and its perceived benefits; C2 - Rationale for the definition of productivity in the context of agile methods; C3 - Empirical verification of agile team productivity factors; C4 - A conceptual framework for agile team productivity factors and their impact; C5 - A team productivity monitoring process considering adaptability and an evaluation of the usefulness of agile team productivity metrics.